Solving conflicting functional requirements by hierarchical structuring—Examples from biological materials. (8th September 2016) - Weinkamer, Richard; Fratzl, Peter
Abstract: Abstract : Hierarchical structure is a hallmark of many biological materials that naturally originate from their growth process, which starts with the biosynthesis of molecular building blocks that self-assemble into larger units. Compartmentalization is used to locally control the synthesis and self-assembly and, thus bridge multiple length scales between the atomistic and macroscopic worlds. Multiscalar structures have the advantage that different physical properties may be adjusted at various structural levels. In particular, when these properties are conflicting, the result can lead to exceptional multifunctional materials. The fiber is a ubiquitous structural motif of biological materials, although its biochemical basis can be diverse. While fibers perform well under tension, they do not under compression. Biological materials are also adaptive and possess self-repair capabilities—properties that require the transport of matter and information. This requires networks of transport and communication that are also hierarchically organized to conciliate the conflicting goals of maximum accessibility and minimal perforation of the material volume. Several examples are discussed in this article.